Administrative Governance In Kludan Village Hall, Tanggulangin Sub-District, Sidoarjo District - Agustina, Isna; Sukmana, Hendra; Muharram, Fajar (Jurnal Administrasi Pemerintahan Desa, 2022)
Research on Administrative Governance at the Kludan Village Hall, Tanggulangin District, Sidoarjo Regency, the author used descriptive research with qualitative research methods. By focusing on narrative explanations, qualitative research seeks to reveal and describe the activities carried out by research subjects, as well as the impact of these actions on their lives [9]. This research is located at the Kludan Tanggulangin Sidoarjo Village Office. The focus of this research uses Daniri's (2005) theory which explains the principles of good administrative governance as measured by indicators 1. Transparency: 2. Accountability 3. Responsibility 4. Independence: and 5. Equality and fairness (Fairness). The Kludan village government has established community participation in village decision making by creating an open framework. Accountability is assessed both through written and verbal accountability. The responsibility of village officials faces problems between private and public interests, often taking a long time. In independence, the village government tries to overcome conflicts of interest, but some still link personal interests in their duties. Finally, equality and fairness face obstacles because some village officials have not fully fulfilled their duties according to their main duties and functions, with the problem of the division of tasks not being clearly defined, giving rise to inequality and unfairness in the management of village administration.